Analisis Analisis Bibliometrik E-Commerce Dalam Bidang Akuntansi - Putra, Vicky Dzaky Cahaya; Harsono, Khaerunisa; Siregar, Ifan Wicaksana (Fakultas Ekonomi Prodi Akuntansi, 2024)
The aim of this research is to analyze reference sources for scientific articles related to e-commerce cited in journals using bibliometric analysis methodology. This research involves data acquisition from scientific articles indexed in the Scopus database. The data was then examined using bibliometric methods, including citation analysis, keyword analysis, and data visualization using VOS Viewer. The use of bibliometric analysis aims to find topics that have not been discussed so that further research can be carried out in the context of e-commerce. The findings are in the form of an overview of developments and a research network that reveals the evolutionary pattern of research on consumer behavior in the context of the digital era. This research contributes to increasing understanding of transformation in the context of digital era consumers.